Analysis of Centelloside of Pegagan (Centella asiatica) - Noverita S. Vinolina; Narendra Singh; Justin A. Napitupulu; Luthfi A. M. Siregar; Marline Nainggolan (Syiah Kuala University, 2013)
Centella asiatica is still categorized as a wild plant that has not undergone domestication. Sustainability of medicinal and aromatic plants for sustainable harvesting of medicinal plants so that it is not only in nature but also the harvest of cultivated so obtained uniform quality. Chemical constituents arealready known: contain some saponin compounds, including asiaticoside, madeccasoside and asiatic acid. This study aims to determine the bioactive content; asiaticoside, madeccasoside and asiatic acid on the top(leaves and petiol) and bottom (roots and tendrils) with HPLC method. The experiment was conducted in growth chamber Department of Biological Sciences and School of Pharmacy Auburn University, USA. This study conducted in September-December 2011. The materials used are Centella asiatica of Deli Serdang accession, Kabanjahe accession, Berastagi accession and Samosir accession. Equipment needed to support the growth chamber study were digital scales, plastic pots, HPLC system types waters alliance 2695 autosampler, 996 photodiode array detector, coulomb adsorbosphere C18 5μ, size 250 x 4.60 mm, UV absorbance, wavelength of 210 nm, flow rate 1.8 ml / min, injection volume of 20 mL, Empower Pro software, and others. The results that the pattern of centelloside (asiaticoside, madecassoside and asiatic acid), when the content of one of the high content of bioactive, the others bioactive will be lower or biosynthetic pattern toward a compound needed. Centelloside plant age affects the content of Centella asiatica. Centelloside pattern is influenced by the condition of the planting medium, very high levels of phosphorus, biosynthesis of centelloside more toward to asiaticoside.